2022
DOI: 10.4314/thrb.v23i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Point prevalence mapping of malaria infection in Rivers State, Nigeria

Abstract: Background: Variations in the risk of malaria across locations exist but are poorly understood though identifying hotspots of malaria transmission will create opportunities for targeted interventions. Point prevalence of malaria in Rivers State was studied using Primary Healthcare Centres (PHCs) as survey points. Methods: The PHCs in Rivers State were geo-referenced using a handheld Global Positioning System (GPS) and 74 were selected across 21 local government areas using systematic grid point sampling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…P. falciparum was the only species of malaria parasite recorded in this study. This finding agrees with the reports from Abah et al (2017), Wogu and Onosakponome (2021), Egbom et al (2021) and Egbom et al (2022) who observed only P. falciparum. In contrast, Nzeako et al (2013) reported the presence of Plasmodium vivax along with P.falciparum.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…P. falciparum was the only species of malaria parasite recorded in this study. This finding agrees with the reports from Abah et al (2017), Wogu and Onosakponome (2021), Egbom et al (2021) and Egbom et al (2022) who observed only P. falciparum. In contrast, Nzeako et al (2013) reported the presence of Plasmodium vivax along with P.falciparum.…”
Section: Discussionsupporting
confidence: 93%
“…An overall malaria prevalence of 51.3% was reported in the study area. This finding agrees with the numbers reported in Rivers State by Egbom and Nzeako (2017), Egbom et al (2021) and Egbom et al (2022), which were 52.5%, 57.4% and 56.3%, respectively. Additionally, the number was higher than that of previous reports in other parts of the State.…”
Section: Discussionsupporting
confidence: 92%
“…Rivers State, in Nigeria's Niger Delta region, is one of the states having a high incidence of malaria cases. Malaria remains endemic in Rivers State [6], [7], [8], [9], [10], [11] with spatiotemporal variations reported [12]. It is a major source of illness and death in Rivers State, despite the availability of efficacious interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Rivers State, in Nigeria's Niger Delta region, is one of the states having a high incidence of malaria cases. Malaria remains endemic in Rivers State [6], [7], [8], [9], [10], [11] with spatiotemporal variations reported [12]. It is a major source of illness and death in Rivers State, despite the availability of efficacious interventions.…”
Section: Introductionmentioning
confidence: 99%